2021
DOI: 10.1155/2021/7396466
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Pain during Rapid Maxillary Expansion (RME): Trends, Anatomical Distinctions, and Age and Gender Correlations

Abstract: Objectives. To investigate pain trends and characteristics of different facial districts in patients undergoing rapid maxillary expansion (RME) and its possible correlations with age and gender. Materials and Methods. 85 subjects (45 males and 40 females) undergoing RME were selected and analyzed during first two weeks of treatment. Patients rated daily two types of pain perception: the general perceived pain (GPP), i.e., the pain overall perceived in the face, and the local perceived pain (LPP), i.e., the pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In orthodontics, the evaluation of PROMs is becoming increasingly important, not only because the patient’s psychosocial well-being improves collaboration during therapy [ 21 ] but also because the results of orthodontic treatment can be improved if the patient is informed and confident about his or her therapy [ 22 , 23 ]. It has been proven that RME often produces discomfort or pain especially during the first week of treatment [ 24 28 ], particularly in girls [ 29 32 ], and it is often associated with an increased age of the child [ 30 , 31 ]. Other studies showed no differences in gender [ 25 , 27 , 33 ] or age [ 27 , 30 , 33 ] of the patients involved in pain experience after RME treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In orthodontics, the evaluation of PROMs is becoming increasingly important, not only because the patient’s psychosocial well-being improves collaboration during therapy [ 21 ] but also because the results of orthodontic treatment can be improved if the patient is informed and confident about his or her therapy [ 22 , 23 ]. It has been proven that RME often produces discomfort or pain especially during the first week of treatment [ 24 28 ], particularly in girls [ 29 32 ], and it is often associated with an increased age of the child [ 30 , 31 ]. Other studies showed no differences in gender [ 25 , 27 , 33 ] or age [ 27 , 30 , 33 ] of the patients involved in pain experience after RME treatment.…”
Section: Introductionmentioning
confidence: 99%